The Oxford handbook of the new private law - Gold, Andrew S. 1973-; Goldberg, John C. P. 1961-; Kelly, Daniel B. ca. 20./21. Jh; Sherwin, Emily 1955-; Smith, Henry E. 1965- (Oxford handbooks online, 2021)
This volume promises to help redefine and reinvigorate the subject of private law, a domain that includes property, contract, and tort law, as well as intellectual property, unjust enrichment, and equity. It emphasizes cross-cutting perspectives and relations between areas of private law, with special attention to the doctrines and structures of the law - an approach now known as 'the New Private Law.'